Tooth size discrepancy in different malocclusion groups in Libya: a pilot study - F Elsheikhi; I Bugaighis; T Hamed (Libyan International Medical University Journal)
Background: Orthodontists need to evaluate intermaxillary tooth size discrepancy (TSD) prior to initiating treatment in order to achieve a stable treatment. Thus, the aim of the present study was to determine the prevalence of TSD in Libyan subjects among different malocclusion groups. Methods: A sample of 60 dental casts of Libyan subjects with different types of malocclusions (Class I, Class II div 1 and Class III) were included in the study. Each malocclusion group (20 dental casts) included equal numbers of males and females, 12-17 years of age. Mesio-Distal tooth measurements were extracted to compute the anterior and overall TSD ratios. Paired Student t-test was used to detect significant discrepancies between the paired teeth measurements. Analysis of Variance (ANOVA) and Tukey Honestly tests were undertaken to detect significant discrepancies among the malocclusion groups. Results: Paired t-test revealed that there were no significant discrepancies between the paired tooth widths except for the upper first molars, upper first premolars, lower lateral incisors and lower canines (P<0.010). ANOVA found no significant differences in the mean anterior TSD ratio in regard to malocclusion groups. However, a significant disparity was noticed in the mean overall TSD ratio among the different malocclusion categories (P<0.04). Conclusion: Statistically significant TSD between the examined malocclusion groups were observed only in the mean overall TSD ratio.